A propensity‐score‐matched analysis of laparoscopic vs open surgery for rectal cancer in a population‐based study. (17th January 2019) - Manchon‐Walsh, P.; Aliste, L.; Biondo, S.; Espin, E.; Pera, M.; Targarona, E.; Pallarès, N.; Vernet, R.; Espinàs, J. A.; Guarga, A.; Borràs, J. M.
Abstract: Aim: The oncological risk/benefit trade‐off for laparoscopy in rectal cancer is controversial. Our aim was to compare laparoscopic vs open surgery for resection of rectal cancer, using unselected data from the public healthcare system of Catalonia (Spain). Methods: This was a multicentre retrospective cohort study of all patients who had surgery with curative intent for primary rectal cancer at Catalonian public hospitals from 2011 to 2012. We obtained follow‐up data for up to 5 years. To minimize the differences between the two groups, we performed propensity score matching on baseline patient characteristics. We used multivariate Cox proportional hazards regression analyses to assess locoregional relapse at 2 years and death at 2 and 5 years. Results: Of 1513 patients with Stage I–III rectal cancer, 933 (61.7%) had laparoscopy (conversion rate 13.2%). After applying our propensity score matching strategy (2:1), 842 laparoscopy patients were matched to 517 open surgery patients. Multivariate Cox analysis of death at 2 years [hazard ratio (HR) 0.65, 95% CI 0.48, 0.87; P  = 0.004] and 5 years (HR 0.61, 95% CI 0.5, 0.75; P  < 0.001) and of local relapse at 2 years (HR 0.44, 95% CI 0.27, 0.72; P  = 0.001) showed laparoscopy to be an independent protective factor compared with open surgery. Conclusions: Laparoscopy results in lower locoregional relapse and long‐term mortality in rectal cancer in unselected patients with all‐risk groups included. Studies using long‐term follow‐up of cohorts and unselected data can provide information on clinically relevant outcomes to supplement randomized controlled trials.